In vitro and ex vivo expression of serum amyloid A3 in mouse lung epithelia. (20th October 2020) - Kawasaki, Haruka; Murakami, Tomoaki; Badr, Yassien; Kamiya, Sato; Shimizu, Kaori; Okada, Ayaka; Inoshima, Yasuo
Abstract: Background and Purpose: Serum amyloid A (SAA), an acute-phase protein whose level tracks infection and inflammation, is the precursor protein of amyloid A (AA) fibrils that is thought to cause AA amyloidosis in human and animals. SAA protein has several isoforms based on the difference of amino acid sequence, such as SAA1 to SAA4 in mice. AA fibrils are associated with chronic inflammation and are mainly originated from SAA1 produced in the liver. SAA3 reportedly contributes to the innate immune response in epithelia; however, little is known about its role at the lung epithelia. Therefore, we investigated SAA3 expression in the lung epithelium activated by bacterial antigens. Materials and Methods: The expressions of SAA3 and SAA1 mRNA were investigated using quantitative real-time PCR, in vitro using mouse Clara (Club) cells and ex vivo using surgically removed mouse lungs, after their stimulation by using either lipopolysaccharide (LPS), the major outer membranous antigen of gram-negative bacteria, or lipoteichoic acid (LTA), the major outer membranous antigen of gram-positive bacteria. In addition, SAA3 and SAA1/2 proteins in treated lung samples were detected by immunohistochemistry (IHC). Results: SAA3 mRNA expression increased in cells and lungs treated with either LPS or LTA. SAA3 mRNA was more sensitively expressed in LPS than LTA treatment. In contrast, SAA1 mRNA expression did not increase by either LPS or LTA treatment. Furthermore, SAA3 mRNA expression increased in a dose-dependent manner in cells treated with tumor necrosis factor-alpha. By IHC, SAA3 protein was highly expressed in the luminal side of the bronchial epithelium, while SAA1/2 was not expressed. Conclusion: These results obtained from in vitro and ex vivo experiments suggest that SAA3 plays an important role in the innate immune response to bacterial infection in the lung epithelia.